2014
DOI: 10.1007/s10545-014-9693-8
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effectiveness of enzyme replacement therapy in children with Gaucher disease: results from the NCS‐LSD cohort study

Abstract: These data provide further evidence of the long-term effectiveness of ERT in children with GD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…In respect to bone crisis, data from the IGGC registry report only 17% of patients with bone crisis [15], from the UK registry study 26% GD1 patients reported bone pain [17], but in our cohort, bone alterations were present in 37.9% (33) of cases, with a clear predominance (50%, 21 cases) in the cohort diagnosed before 1994 than the patients diagnosed after ERT became available. This is a clear feature of a more severe presentation in our country.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In respect to bone crisis, data from the IGGC registry report only 17% of patients with bone crisis [15], from the UK registry study 26% GD1 patients reported bone pain [17], but in our cohort, bone alterations were present in 37.9% (33) of cases, with a clear predominance (50%, 21 cases) in the cohort diagnosed before 1994 than the patients diagnosed after ERT became available. This is a clear feature of a more severe presentation in our country.…”
Section: Discussionmentioning
confidence: 67%
“…The large studies are supported by statistics extrapolating modelling-based studies from data from the International Collaborative Gaucher Group Registry (ICGGR) [15, 16] and several works from national cooperative groups that have summarize information from different cohorts [1721]. However, the disease manifestations are impacted by the ethnicity/population characteristics and it is important to analyze what we have achieved in every-day clinical practice with current treatment and how the behavior of the disease has changed in the pediatric population, especially in children treated from the first years of life.…”
Section: Introductionmentioning
confidence: 99%